1999
DOI: 10.1034/j.1399-3089.1999.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Human–porcine receptor–ligand compatibility within the immune system: relevance for xenotransplantation

Abstract: Immune responses to xenografts are likely to be highly dependent on the efficiency of molecular interactions between the donor and the recipient species. This brief review summarizes what is currently known about the compatibilities across the human-porcine species barrier of the molecular interactions that are important in the immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…The latter relies on the efficiency of donor cell-mediated central deletion of donor antigen-reactive T cells in the recipient thymus. Although cross-species incompatibilities in adhesion molecules may limit the thymic homing of donor cells in discordant xenogeneic recipients, [35][36][37][38] such defects have not been detected in a highly disparate pig-to-mouse combination. We have previously shown that long-term repopulation of host thymus with SLA class II ϩ cells can be achieved in NOD/SCID-Tg mice by porcine BMT, 20 and that the induction of porcine hematopoietic chimerism is capable of inducing T-cell tolerance to porcine hematopoietic donor antigens in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The latter relies on the efficiency of donor cell-mediated central deletion of donor antigen-reactive T cells in the recipient thymus. Although cross-species incompatibilities in adhesion molecules may limit the thymic homing of donor cells in discordant xenogeneic recipients, [35][36][37][38] such defects have not been detected in a highly disparate pig-to-mouse combination. We have previously shown that long-term repopulation of host thymus with SLA class II ϩ cells can be achieved in NOD/SCID-Tg mice by porcine BMT, 20 and that the induction of porcine hematopoietic chimerism is capable of inducing T-cell tolerance to porcine hematopoietic donor antigens in mice.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Thus, the host thymus-homing capacity of donor cells would be an important determinant for tolerance induction by mixed chimerism across discordant xenogeneic barriers. Although cross-species incompatibilities in adhesion molecules may limit the thymic homing of donor cells in discordant xenogeneic recipients, [32][33][34][35] such defects have not been detected in the highly disparate pig-to-mouse combination. We have previously shown that long-term (Ͼ 20 weeks) repopulation of host thymus with porcine class II ϩ cells can be achieved in NOD/ SCID-Tg mouse recipients of porcine BM (without subsequent mouse BMT).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, a prerequisite for the capture of human NK cells from the circulation onto porcine EC are receptor±ligand interactions between adhesion molecules. While in vitro experiments using human T cell or heterogenous leukocyte populations have shown that several such interactions are intact across the human±porcine species barrier (reviewed in [20,21]), this review will focus on and summarize the current knowledge on the adhesive interactions between human NK cells and porcine EC.…”
Section: Introductionmentioning
confidence: 99%